Regulation of drug-metabolizing enzymes and efflux transporters by Astragali radix decoction and its main bioactive compounds: Implication for clinical drug–drug interactions. (2nd March 2016) - Zhang, Guiyu; Ou, Rilan; Li, Fangyuan; Wu, Jinjun; Zheng, Liang; Tong, Yunli; Liu, Yuting; Liu, Zhongqiu; Lu, Linlin
Abstract: Ethnopharmacological relevance: Astragali radix ("Huang Qi" in Chinese, HQ) is a well-known traditional Chinese herbal medicine that possesses various biological functions. Astragaloside IV (AS-IV), calycosin (CS), and formononetin (FMNT) are the three main bioactive compounds of HQ that are responsible for its pharmacological activities and therapeutic efficacy. Aim of the study: This study aims to investigate the effects of HQ, AS-IV, CS, and FMNT on major human drug-metabolizing enzymes (DMEs), including CYP3A4, CYP2B6, CYP2E1, UGT1A, UGT1A6, SULT1A1, and SULT1A3, as well as efflux transporters (ETs), including P-gp, MRP2, BCRP, MRP1, and MRP3, by using HepG2 cell line. Results would provide beneficial information for the proper clinical application of HQ. Materials and methods: HepG2 cells were treated with HQ, AS-IV, CS, and FMNT for 96 h. Cell viability was examined by MTT assay. The protein and mRNA levels of DMEs and ETs were measured using Western blot and real-time PCR, respectively. Results: Compared with the control group, HQ considerably increased the expression levels of CYP3A4, CYP2B6, CYP2E1, UGT1A, P-gp, MRP2, BCRP, and MRP3 in a dose-dependent manner. Inversely, HQ significantly decreased the protein levels of UGT1A6, SULT1A1, and MRP1. Exposure to AS-IV induced the protein levels of UGT1A, P-gp, MRP1, and MRP3, but produced inhibitory effects on CYP3A4, CYP2B6, and BCRP. The expression levels of CYP3A4, UGT1A, SULT1A1, P-gp, MRP2, and MRP3 were remarkably increased in the CS-treated cells, whereas the protein levels of SULT1A3 and BCRP were decreased. FMNT treatment induced the protein levels towards CYP3A4, CYP2B6, UGT1A, P-gp, MRP1, MRP2, and MRP3, but inhibited the expression of CYP2E1, SULT1A1, and SULT1A3. Conclusions: HQ and its main bioactive compounds, including AS-IV, CS, and FMNT significantly regulated the expression of the major DMEs and ETs. HQ produced stronger regulations (induction or inhibition) on DMEs and ETs than AS-IV, CS, or FMNT alone. The results indicate that potential drug–drug interactions might exist when the tested drugs, specifically HQ, are co-administered with other substrate drugs that are metabolized or transported via the studied DMEs or ETs. This study provides beneficial information for appropriate use of HQ for clinical therapy. Graphical abstract: